Compound words prompt arbitrary semantic associations in conceptual memory - Boutonnet, Bastien; Mcclain, Rhonda; Thierry, Guillaume (Frontiers in Psychology, 2014)
Linguistic relativity theory has received empirical support in domains such as colour perception and object categorisation. It is unknown however, whether relations between words idiosyncratic to language impact nonverbal representations and conceptualisations. For instance, would one consider the concepts of horse and sea as related were it not for the existence of the compound seahorse? Here, we investigated such arbitrary conceptual relationships using a non-linguistic picture relatedness task in participants undergoing event-related brain potential recordings. Picture pairs arbitrarily related because of a compound and presented in the compound order elicited N400 amplitudes similar to unrelated pairs. Surprisingly, however, pictures presented in the reverse order (as in the sequence horse – sea) reduced N400 amplitudes significantly, demonstrating the existence of a link in memory between these two concepts otherwise unrelated. These results break new ground in the domain of linguistic relativity by revealing predicted semantic associations driven by lexical relations intrinsic to language.